Soul-foods as pharmaka: female bodies and poisons in the Upper Rio Negro - Pedro Lolli; Geraldo Andrello (Journal de la Société des Américanistes)
In this article, we explore the origins, properties, and ritual uses of a series of psychoactive substances among indigenous peoples of the Upper Rio Negro. Setting out from the mythical genesis of tobacco, coca, paricá, and caapi (ayahuasca), we examine the relationship between these substances and diverse aspects of female bodies and their reproductive powers, suggesting that these psychoactives can be conceived as pharmaka in the classic sense of the term, acting both to increase a person’s vital force and/or to harm and kill. As we show, these effects relate to the practice of blown magical incantations, used to both cure and provoke diseases, a connection that allows us to explore indigenous notions of life force, speech, and breath as ways through which bodies affect each other.